Dynamic causal chain of money, output, interest rate and prices in Malaysia: evidence based on vector error- correction modelling analysis - Tan, Hui Boon; Baharumshah, Ahmad Zubaidi (Taylor & Francis, 1999)
The dynamic causal chain among money, real output, interest rate, and inflation is Reexamined in the context of a small fast-growing economy using the recently developed techniques of Johansen's multivariate conitegration analysis followed by vector error-correction modelling, Granger causality, variance decompositions, and impulse response functions. The results of the multivariate cointegration tests suggested a stable long-run equilibrium relationship exists among these macroeconomic variables. The short-run results based on vector error-correction modeling, on the other hand, support the New Keynesians' view that money is non- neutral, at least in the short-run. It also indicates that monetary policy can contribute to the stability of domestic prices. M1, among the various definitions of money stock, has been identified as the most effective intermediate monetary target to curb inflation. M3, in turn, has been suggested as the most appropriate intermediate target to promote sustainable economic growth with contained inflation. For this economy, the deviation of the macroeconomic activity from its long-run equilibrium is adjusted through changes in the money stock and prices [E44].